Dampak Pembangunan Tahap 1 Revitalisasi Pasar Kembang Kalisari Berdasarkan Pendapat Masyarakat Sekitarnya - Reksa Istiana; Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
The revitalization on Pasar Kembang Kalisari is an effort to overcome the declining of environment quality around the market. The revitalization is done in two stages of development which the first stage has been finished. A development certainly will generate some changes or impacts that affect the community, especially the community around the area. The purpose of this research is to review the impacts of the first stage of development from the revitalization on Pasar Kembang Kalisari based on the opinion of its surrounding community, especially the impacts to the environment and social-economy during and after the development is done. The method used in this research is quantitative. This research is supported with sampling proportionate stratified random sampling technique. The community said that the positive impacts during the first stage development of Pasar Kembang Kalisari are the employment opportunity, community’s economy and income enhancement, the increasing of surroundings aestheticism and comfort, and the transformation of becoming tourist site (Kampung Pelangi). Moreover the negative impacts are the pollution caused by the construction around the location and the income derivation of the florist, and the alteration of livelihood for some who provide repair shop.